Full Research Correlation and Path Analysis Studies for Growth and Yield Contributing Traits in Indian Mustard (Brassica juncea L.) - Ray, K.; Pal, A. K.; Banerjee, H.; Phonglosa, A. (International Journal of Bio-resource and Stress Management, 2023)
A study was undertaken at West Bengal, India with Indian mustard var. varuna, during winter season of 2010-11 and 2011-12 in a split-plot design with three levels of irrigation (main-plots) and four levels of sulphur (sub-plots) with three replications. Experimental results revealed that application of two irrigations at 30 and 60 DAS, along with 45 kg S ha-1 influenced growth attributes and seed yield significantly. Further increase in S level upto 60 kg ha-1 although gave higher seed yield but the difference was non-significant. Highest consumptive use of water was recorded with two irrigations (at 30 and 60 DAS) while it was increased slightly with increase in S levels from 0 to 60 kg ha-1. Sulphur @ 45 kg ha-1 recorded highest water use efficiency at all irrigation levels. Irrigation (twice at 30 and 60 DAS) fetched higher net return over single irrigation. At all irrigation levels, 45 kg S ha-1 recorded the highest net return and B:C ratio. Seed yield showed positive significant correlation with all the independent variables and CGR revealed the highest degree of correlation followed by RGR, NAR, plant height and number of primary branches plant-1. It is obvious from path analysis that RGR had highest direct and positive effect on seed yield followed by CGR and number of primary branches plant-1. Thus CGR, RGR and NAR were under genotypic control and this positive correlation toward seed yield would be favourable to breeder for genetic improvement of Indian mustard.